Spherical chitosan nanoparticle and preparation method thereof
The preparation of spherical chitosan nanoparticles at the nanoscale through reverse phase microemulsion method and ultrasonic technology has solved the problem of difficult to prepare uniform morphology in the prior art, and achieved efficient preparation of adjustable particle size and stability.
Patent Information
- Application Number
- CN202411861819.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to efficiently prepare spherical chitosan nanoparticles with uniform morphology, especially in controlling nanoscale and particle morphology uniformity.
The reverse phase microemulsion method was used to construct a water-in-oil microemulsion system of dichloromethane and chitosan solution, and the cross-linking and curing was added in ultrasonic state to form spherical chitosan nanoparticles. The excess ingredients were removed by dialysis and the nanoparticles were purified.
It has achieved efficient preparation of spherical chitosan nanoparticles with excellent morphology and adjustable particle size, with good pH stability and long-term stability, and is suitable for different application scenarios.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of drug delivery, and more particularly to spherical chitosan nanoparticles and a preparation method thereof. Background Art
[0002] Chitosan is a natural linear polysaccharide cationic hydrophilic polymer with abundant hydroxyl (-OH) and amine (-NH2) functional groups in its structure, which can react with cross-linking agents to form films or spheres by chemical cross-linking in situ. By further preparing chitosan into chitosan nanoparticles, while retaining the excellent properties of chitosan, the high specific surface area and unique small size effect of nanomaterials can be used to significantly improve its physical and chemical properties and biological effects.
[0003] The preparation methods of chitosan nanoparticles mainly include ionic crosslinking, precipitation, spray drying and reverse microemulsion, but since chitosan is a natural linear polysaccharide cation, the existing technical solutions still face huge technical challenges in the preparation of high-quality chitosan nanoparticles with spherical morphology.
[0004] Prior art CN108014344A successfully prepared chitosan nano drug carriers with dual response to pH and temperature by cyclodextrinized chitosan using sodium tripolyphosphate-mediated ionic crosslinking method, which can be applied to targeted delivery of nano drugs. However, although chitosan nanoparticles can be prepared simply and quickly using the ionic crosslinking method, it is difficult to achieve precise control of the morphology of chitosan nanoparticles, and flocculent precipitation is prone to occur, resulting in preparation failure.
[0005] The prior art CN115444835A dissolves chitosan in an acidic aqueous solution, then adds trivalent iron salt, and adjusts the pH value of the solution to 7.0 while stirring, so that chitosan is precipitated together with trivalent iron ions. However, it is also difficult to efficiently prepare spherical chitosan nanoparticles with relatively uniform morphology using the precipitation method, and the precise requirement for pH value during the synthesis process also limits the preparation of certain composite chitosan nanoparticles.
[0006] In the prior art CN104525071A, the chitosan solution is atomized and dispersed into fine droplets under the action of electrostatic force by electrostatic spraying, and the solvent is volatilized in the air to form a microsphere morphology, which is finally received by the emulsified crosslinking agent and obtained through centrifugal separation, ethanol washing and other steps. However, the spray drying method for preparing chitosan nanoparticles has high requirements for equipment. Due to the limitation of the precision of the atomizing nozzle process, it is difficult to prepare chitosan nanoparticles with a particle size below 200nm.
[0007] Prior art CN106214666A uses grafted chitosan as a stabilizer / stabilizer and N,N-methylenebisacrylamide as a cross-linking agent to successfully carry out inverse mini-emulsion polymerization, and uses this to load water-soluble drugs to form drug nano sustained-release particles. Although the microemulsion method can prepare spherical chitosan nanoparticles well by means of the surface tension of the liquid, it still faces huge technical challenges in the control of nanometer level and uniform particle morphology. In addition, the oil phase medium used in the inverse microemulsion method may also have the risk of contaminating the sample. Therefore, a new chitosan nanoparticle preparation technology is still needed to meet the needs of practical applications. Summary of the invention
[0008] The present invention provides a spherical chitosan nanoparticle to overcome the defect that it is difficult to obtain nano chitosan particles with uniform particle morphology in the prior art.
[0009] Another object of the present application is to provide a method for preparing spherical chitosan nanoparticles.
[0010] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0011] A method for preparing spherical chitosan nanoparticles comprises the following steps:
[0012] S1, adding dichloromethane and Tween 80 to the chitosan solution and mixing evenly;
[0013] S2, under ultrasonic condition, after adding sodium tripolyphosphate solution, continue ultrasonic treatment;
[0014] S3, after sufficient reaction in the buffer, removing the dichloromethane oil phase;
[0015] S4, taking the supernatant by centrifugation, removing Tween 80 in the supernatant, and obtaining spherical chitosan nanoparticles.
[0016] Preferably, chitosan is dissolved in an aqueous solution of glacial acetic acid, vortexed to dissolve until transparent, then the pH value of the solution is adjusted to 6.0 using a sodium hydroxide solution, filtered using a hydrophilic filter membrane with a pore size of 0.22 microns, and the chitosan solution is obtained after adjusting the concentration.
[0017] Preferably, the volume ratio of the glacial acetic acid aqueous solution is 1%, and the concentration of the sodium hydroxide solution is 0.3 mol / L.
[0018] Preferably, the chitosan solution is added into dichloromethane and Tween 80 and mixed evenly, and then subjected to ultrasonic treatment.
[0019] Preferably, after uniform mixing, ultrasonic treatment is performed for 1 to 5 minutes.
[0020] Furthermore, the chitosan solution is prepared from chitosan with a viscosity of 100 to 500 mPa·s.
[0021] Preferably, the chitosan solution is prepared from chitosan having a viscosity of 100 to 200 mPa·s.
[0022] Furthermore, the concentration of the chitosan solution is 0.02-2.0 mg / mL.
[0023] Preferably, the concentration of the chitosan solution is 1.0 mg / mL.
[0024] Furthermore, the concentration of the added sodium tripolyphosphate solution is 0.03 to 3.0 mg / mL.
[0025] Preferably, the concentration of the sodium tripolyphosphate solution is 0.4-3.0 mg / mL.
[0026] Preferably, the concentration of the sodium tripolyphosphate solution is 0.7 mg / mL.
[0027] When preparing spherical chitosan nanoparticles with a particle size greater than 800 nm, the concentration of sodium tripolyphosphate is not greater than 0.7 mg / mL, and the concentration of the chitosan acid solution is not less than 0.5 mg / mL; when preparing spherical chitosan nanosphere particles with a particle size less than 200 nm, the concentration of sodium tripolyphosphate is not less than 0.03 mg / mL, and the concentration of the chitosan acid solution is not greater than 0.3 mg / mL.
[0028] Preferably, after adding the sodium tripolyphosphate solution, ultrasonic treatment is performed for 1 to 3 minutes.
[0029] Further, the volume ratio of dichloromethane to Tween 80 is 100:1-5;
[0030] Preferably, the volume ratio of dichloromethane to Tween 80 is 200:5.
[0031] Furthermore, the ratio of dichloromethane to chitosan solution is 200:10-20.
[0032] Preferably, the ratio of dichloromethane to chitosan solution is 200:16.
[0033] Furthermore, the volume ratio of chitosan to sodium tripolyphosphate is 8:1-4.
[0034] Furthermore, the volume ratio of chitosan to sodium tripolyphosphate is 4:1.
[0035] Preferably, the buffer is a phosphate buffer with a pH of 6.
[0036] Preferably, the reaction is stirred at 150 r / min for 12 h.
[0037] Furthermore, in S4, Tween 80 in the supernatant was removed by dialysis.
[0038] Preferably, the supernatant is collected after centrifugation at 4500 r / min for 10 min.
[0039] Preferably, the supernatant is dialyzed with ultrapure water for 7 hours under stirring, with the ultrapure water being replaced every hour, and after 3 hours, the ultrapure water is replaced every 2 hours.
[0040] A spherical chitosan nanoparticle is prepared by the preparation method.
[0041] Furthermore, the particle size of the spherical chitosan nanoparticles is 50 to 1000 nm.
[0042] Preferably, the particle size of the spherical chitosan nanoparticles is 50 to 300 nm.
[0043] Preferably, the particle size of the spherical chitosan nanoparticles is 50 to 200 nm.
[0044] Preferably, the pH value of the storage environment of the spherical chitosan nanoparticles is 3-8.
[0045] The present invention utilizes the reverse microemulsion method to construct an organic phase based on dichloromethane and an aqueous phase system mainly composed of a chitosan solution, so that the chitosan solution can form an oil-in-water type microemulsion system. At the same time, an ultrasonic dispersion technology is introduced in the preparation process, and tiny reverse microemulsion droplets are formed by means of the cavitation effect of ultrasonic waves. And by adding a non-ionic surfactant Tween 80, the spherical quality and uniformity of the particle size of the reverse microemulsion droplets can be further improved. On this basis, sodium tripolyphosphate is continuously added to the microemulsion system after ultrasonic dispersion for cross-linking and curing to form spherical chitosan nanoparticles. Finally, the remaining redundant components in the reaction system are removed by dialysis to purify the chitosan nanoparticles.
[0046] Compared with the existing chitosan nanoparticle preparation technology, the preparation method of the present invention can prepare spherical chitosan nanoparticles with excellent morphology, and can achieve efficient preparation of spherical chitosan nanoparticles with a particle size in the range of 50 to 1000 nanometers, and has good adaptability.
[0047] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0048] 1. Excellent morphology, the particle size of the prepared chitosan nanoparticles can be controlled by parameters. The prepared chitosan nanoparticles have good spherical morphology, uniform shape and excellent dispersibility. The average particle size can be adjusted in the range of 50 to 1000 nm to meet the needs of different application scenarios.
[0049] 2. Good pH stability. In the pH range of 3.0 to 8.0, the particle size and dispersion state of spherical chitosan nanoparticles are relatively stable and adaptable to a wide range of solution environments. Under strong acid (pH < 3.0) or strong base (pH > 8.0) conditions, the particle size changes significantly, but this performance still meets the needs of most biomedical applications.
[0050] 3. High long-term stability. The prepared chitosan nanoparticles showed no obvious change in particle size and no aggregation and precipitation at room temperature for 5 days. The stability of Zeta potential under pH 7.4 further demonstrated its good dispersibility and solution stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is a scanning electron microscope morphology observation photo;
[0052] Figure 2 Particle size of spherical chitosan nanoparticles prepared for different concentrations of chitosan (a) and sodium tripolyphosphate (b);
[0053] Figure 3 Particle size (a) and surface potential (b) of spherical chitosan nanoparticles prepared with chitosan of different viscosities;
[0054] Figure 4 The particle size of spherical chitosan nanoparticles prepared under different pH conditions;
[0055] Figure 5 The particle size (a) and surface potential (b) of spherical chitosan nanoparticles placed at room temperature for different time periods;
[0056] Figure 6 The photos of spherical chitosan nanoparticles prepared by 100-200mPa·s (a) and 400mPa·s (b) chitosan were placed for different time periods;
[0057] Figure 7 Light absorption curves of spherical chitosan nanoparticles prepared with chitosan of 100-200 mPa·s (a) and 400 mPa·s (b) after being placed for different time periods. DETAILED DESCRIPTION
[0058] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0059] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0060] Example 1
[0061] Chitosan powder with a pH of 400 mPa·s was prepared into a chitosan solution (0.1 mg / mL) with a pH of 6 using a 1% acetic acid solution, and a disposable needle filter (0.22 μm) was used to remove insoluble particles. In the preparation of nano-chitosan spheres, 125 μL of Tween 80 was added to 5 mL of dichloromethane and vortexed, and 400 μL of the chitosan solution was added and ultrasonicated for 2 min. Then, 100 μL of sodium tripolyphosphate solution (0.7 mg / mL) was added under ultrasonication and ultrasonication for 1 min to obtain reverse microemulsion droplets. Finally, 20 mL of phosphate buffer with a pH of 6 was added under magnetic stirring in a fume hood at 150 r / min for 12 h to cross-link chitosan with sodium tripolyphosphate and release the dichloromethane oil phase. The chitosan nano-solution was centrifuged at a centrifugal rate of 4500 r / min for 10 min, and the supernatant was taken and placed in a dialysis bag, and dialyzed 5 times with ultrapure water under stirring to remove the Tween component. Ultrapure water was replaced every 1 h in the first 3 dialysis sessions and every 2 h in the last 2 dialysis sessions. Spherical chitosan nanoparticles in a dispersed state were obtained after 7 h of dialysis.
[0062] Example 2
[0063] Chitosan powder with a pH of 500 mPa·s was prepared into a chitosan solution (0.1 mg / mL) with a pH of 6 using a 1% acetic acid solution, and a disposable needle filter (0.22 μm) was used to remove insoluble particles. In the preparation of nano-chitosan spheres, 250 μL of Tween 80 was added to 5 mL of dichloromethane and vortexed, and 400 μL of the chitosan solution was added and ultrasonicated for 2 min. Then, 200 μL of sodium tripolyphosphate solution (0.7 mg / mL) was added under ultrasonication and ultrasonication for 1 min to obtain reverse microemulsion droplets. Finally, 20 mL of phosphate buffer with a pH of 6 was added at 150 r / min and magnetically stirred in a fume hood for 12 h for sodium tripolyphosphate cross-linking chitosan and releasing dichloromethane oil phase. The chitosan nano-solution was centrifuged at a centrifugal rate of 4500 r / min for 10 min, and the supernatant was taken and placed in a dialysis bag, and dialyzed 5 times with ultrapure water under stirring to remove the Tween component. Ultrapure water was replaced every 1 h in the first 3 dialysis sessions and every 2 h in the last 2 dialysis sessions. Spherical chitosan nanoparticles in a dispersed state were obtained after 7 h of dialysis.
[0064] Example 3
[0065] The preparation scheme of Example 3 is similar to that of Example 1, except that chitosan powder with a viscosity of 100 to 200 mPa·s is used.
[0066] Example 4
[0067] The preparation scheme of Example 4 is similar to that of Example 1, except that chitosan powder with a viscosity of 100-200 mPa·s is used, and the concentrations of the added chitosan solutions are 0.03 mg / mL, 0.1 mg / mL, 0.3 mg / mL, 0.5 mg / mL, 0.7 mg / mL, and 0.9 mg / mL, respectively.
[0068] Example 5
[0069] The preparation scheme of Example 5 is similar to that of Example 1, except that chitosan powder with a viscosity of 100-200 mPa·s is used, and the concentrations of the added sodium tripolyphosphate solution are 0.03 mg / mL, 0.1 mg / mL, 0.3 mg / mL, 0.5 mg / mL, 0.7 mg / mL, and 0.9 mg / mL, respectively.
[0070] Example 6
[0071] The preparation scheme of Example 6 is similar to that of Example 1, except that the volume ratio of dichloromethane: Tween 80: chitosan solution: sodium tripolyphosphate solution added is 200:2:16:2.
[0072] Detection Methods
[0073] 1. Morphology observation
[0074] The prepared spherical chitosan nanoparticles were observed by field emission scanning electron microscopy.
[0075] 2. Particle size detection
[0076] The particle size of the obtained spherical chitosan nanoparticles was detected using a scanning electron microscope and a particle size analyzer.
[0077] 3. pH stability test
[0078] Phosphate buffers with different acid-base gradients were prepared to have pH values of 2, 3, 4, 5, 6, 7, 8, and 9, respectively. The spherical chitosan nanoparticles prepared above were added to the phosphate buffers with different pH values and incubated for 24 hours.
[0079] 4. Long-term stability testing
[0080] (1) After being placed for 1 day, 2 days, 3 days, 4 days, and 5 days, the particle size and surface potential changes of each group of samples were detected.
[0081] (2) The spherical chitosan nanoparticle solution prepared from 100-200 mPa·s chitosan in Example 4 and the spherical chitosan nanoparticle solution prepared from 400 mPa·s chitosan were divided into two groups and left to stand at room temperature for 5 days. The ultraviolet absorption changes of the two groups of samples were observed and detected on the first, third and fifth days.
[0082] Test results
[0083] The results are as follows Figure 1 As shown, the chitosan nanoparticles prepared in Example 2 have good spherical morphology and good dispersibility as measured by field emission scanning electron microscopy, and the average particle size is about 50 nm.
[0084] The particle size of the spherical chitosan nanoparticles prepared at different concentrations in Examples 4 to 5 was tested. Figure 2 The results showed that when the concentration of sodium tripolyphosphate was constant, before the concentration of chitosan acid solution was 0.5 mg / mL, the size of the prepared spherical chitosan nanoparticles increased with the increase of the concentration of chitosan acid solution. From 0.5 mg / mL onwards, the increase in the size of the spherical chitosan nanoparticles decreased ( Figure 2 a); When the chitosan concentration is constant, as the concentration of sodium tripolyphosphate increases, the particle size of spherical chitosan nanoparticles decreases ( Figure 2 b). When preparing spherical chitosan nanoparticles with a particle size greater than 800 nm, the concentration of sodium tripolyphosphate is not greater than 0.7 mg / mL, and the concentration of chitosan acid solution is not less than 0.5 mg / mL; when preparing spherical chitosan nanoparticles with a particle size less than 200 nm, the concentration of sodium tripolyphosphate is not less than 0.03 mg / mL, and the concentration of chitosan acid solution is not greater than 0.3 mg / mL. Spherical chitosan nanoparticles with smaller particle sizes can be used for applications requiring high dispersibility and low size, such as drug delivery and targeted therapy, and spherical chitosan nanoparticles with smaller particle sizes can be used for applications requiring high mechanical stability, such as membrane separation and biosensing.
[0085] The results are as follows Figure 3 As shown, in Example 4 (chitosan 0.1 mg / mL), the average particle size of spherical chitosan nanoparticles prepared from 100-200 mPa·s chitosan solution is 129 nm, and the Zeta potential is -3.5 mV. The average particle size of spherical chitosan nanoparticles prepared using 400 mPa·s chitosan as raw material in Example 1 is 81 nm, and the Zeta potential is 3.19 mV. If spherical chitosan nanoparticles with a particle size less than 150 nm are prepared, the viscosity of the chitosan solution is greater than 100 mPa·s. Under the same conditions, spherical chitosan nanoparticles prepared using high-viscosity chitosan raw materials have a smaller particle size, and their charge is determined by the type of chitosan raw material used. Positively charged particles can interact with negatively charged molecules (such as DNA, RNA, proteins, etc.), and are more suitable for targeted delivery of negatively charged biomolecules. Negatively charged particles can bind to positively charged compounds or be used to avoid nonspecific interactions with negatively charged cell membranes, and have unique advantages in certain anticoagulant and antibacterial applications.
[0086] In Example 6, the higher chitosan ratio and lower sodium tripolyphosphate ratio slightly affect the degree of crosslinking, and the lower surfactant ratio also causes the emulsion droplet size to be larger than that of Example 1, thereby affecting the particle size of the spherical chitosan nanoparticles. After incubation of Example 6, the particle size detection results are as follows: Figure 4 As shown in the figure, when the pH value of the solution is lower than 3.0, chitosan nanoparticles dissolve in the buffer solution and the particle size gradually decreases. When the pH value of the solution is higher than 8, the ion concentration and charge shielding effect under alkaline conditions cause the surface charge distribution of chitosan nanoparticles to change, resulting in the shrinkage of chitosan nanoparticles and a decrease in particle size. Spherical chitosan nanoparticles are relatively stable in the pH range of 3.0 to 8.0.
[0087] like Figure 5 As shown, the spherical chitosan nanoparticle samples prepared in Example 1 and Example 3 have no obvious change trend in the particle size of the nanoparticles after being placed at room temperature for 5 days ( Figure 5 a), indicating that the sample maintained good dispersion during storage and had good stability. On the other hand, in phosphate buffer with a pH of 7.4, the Zeta potential of the spherical chitosan nanoparticle sample showed a relatively stable negative charge ( Figure 5 b) Because at this pH, the amino groups on chitosan can be deprotonated or the chitosan raw material itself has negatively charged functional groups. This stable surface charge state of the nanoparticles allows the chitosan nanoparticles to always maintain a mutually exclusive state in the solution due to their like-charged state, which is beneficial for maintaining good dispersibility of the chitosan nanoparticle sample.
[0088] like Figure 6 As shown in the figure, the spherical chitosan nanoparticle solutions prepared from chitosan with different viscosities in Example 1 and Example 3 can maintain good stability within five days, and no obvious aggregation and precipitation of chitosan nanoparticles can be observed in the solution. Accordingly, the absorption curves of the two groups of chitosan spherical nanoparticle solutions remained consistent during the five-day storage period ( Figure 7 ), indicating that the optical properties of the solution remain consistent, without turbidity, precipitation or other optical changes, indicating that the chitosan molecular structure is stable, the dispersion state is good, no aggregation precipitation occurs, and the solution remains stably dissolved. This stability has important application prospects for the effectiveness and reliability of chitosan in biomedicine, drug delivery and other applications.
[0089] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing spherical chitosan nanoparticles, characterized in that: The following steps are involved: S1, adding dichloromethane and Tween 80 to the chitosan solution and mixing evenly; S2, under ultrasonic condition, after adding sodium tripolyphosphate solution, continue ultrasonic treatment; S3, after sufficient reaction in the buffer, removing the dichloromethane oil phase; S4, taking the supernatant by centrifugation, removing Tween 80 in the supernatant, and obtaining spherical chitosan nanoparticles.
2. The method for preparing spherical chitosan nanoparticles according to claim 1, characterized in that: The chitosan solution is prepared from chitosan with a viscosity of 100 to 500 mPa·s.
3. The method for preparing spherical chitosan nanoparticles according to claim 1, characterized in that: The concentration of the chitosan solution is 0.02-2.0 mg / mL.
4. The method for preparing spherical chitosan nanoparticles according to claim 1, characterized in that: The concentration of the added sodium tripolyphosphate solution is 0.03-3.0 mg / mL.
5. The method for preparing spherical chitosan nanoparticles according to claim 1, characterized in that: The volume ratio of dichloromethane to Tween 80 is 100:1-5.
6. The method for preparing spherical chitosan nanoparticles according to claim 1, characterized in that: The volume ratio of dichloromethane to chitosan solution is 200:10-20.
7. The method for preparing spherical chitosan nanoparticles according to claim 1, characterized in that: The volume ratio of chitosan to sodium tripolyphosphate is 8:1-4.
8. The method for preparing spherical chitosan nanoparticles according to claim 1, characterized in that: In S4, Tween 80 in the supernatant was removed by dialysis.
9. A spherical chitosan nanoparticle, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. The spherical chitosan nanoparticles according to claim 9, characterized in that: The particle size is 50~1000nm.
Citation Information
Patent Citations
Chitosan nano-microspheres product and preparation method thereof
CN101675996A
Preparation method and application of chitosan nanoparticles with pore structures
CN102921013A
Chitosan microsphere preparation method
CN104525071A
Method for forming medicament slow-release nanoparticles from inverse miniemulsion
CN106214666A
Chitosan nano drug carrier with pH and temperature response and preparation method and application thereof
CN108014344A